Ἀρχαῖοι μῦθοι or λόγοι δυνάμενοι? The Mythical History and its Political Impact under the Argead Dynasty - Díaz-Fernández, Alejandro (My University, 2019)
According to a passage from Aeschines’ speech On the embassy, when Athenians sent a delegation to Philip to negotiate the peace in 346, the envoys defended the Athenian dominion over Amphipolis and the so-called Ἐννέα Ὁδοί by claiming that one of the sons of Theseus had received the land as the dowry of his wife. Aeschines nonetheless stresses that the embassy did not only adduce ἀρχαῖοι μῦθοι, but also more convincing arguments based on recent deeds (Aeschin. 2.31). Shortly after Aeschines was prosecuted by his role in the embassy, Speusippus, Plato’s nephew and his successor as the director of the Academy, sent to Philip a controversial letter in which he justifies some of the recent conquests of the Macedonian king (Amphipolis included) by means of mythical stories that Speusippus defines as λόγοι δυνάμενοι τὴν σὴν ἀρχὴν ὠφελεῖν (Speus. Phil. 8), “strong arguments in support of your rule” (translation by A. F. Natoli, The Letter of Speusippus to Philip, Stuttgart, 2004, 107). Speusippus’ asseveration clash with Aeschines’ commentary, leading us to wonder about the actual value of the mythical history in such controversies. The question is particularly relevant in the case of the Argead dynasty, whose kings repeatedly made use of the myth to draw the remote past of Macedonia and to support their political aspirations within the Greek world. In sum, this paper focuses on the use of the myth both in the historical narrative and in the political discourse by the Argead kings, from Alexander Philohelenus to the rise of Alexander the Great.
Keywords: Mitología; Ancient Macedonia; Greek Mythology; Ancient Greece; Greek Historiography